A Preliminary Ruling Instrument in the Constitutional Jurisprudence of Lithuania - Griciūnas, Paulius (Teisė, 2019)
The judicial dialogue between the Constitutional Court of the Republic of Lithuania and the European Court of Justice is analyzed in this article. The variety of opinions, arguments, and the evolution of the approaches regarding the right or obligation of the Constitutional Court to refer for a preliminary ruling are researched. Major events in the evolution were two referrals by the Constitutional Court in 2007 and 2017; both of these decisions to refer for the preliminary ruling are compared, and the similarities and differences analyzed. The potential of a preliminary ruling in the constitutional jurisprudence is demonstrated, with an emphasis on the indirect control of the legality of EU acts and the national identity clause.
Keywords: Constitutional Court; EU law; national identity; preliminary ruling